Divergent formation pathways of soil particulate and mineral-associated organic carbon across soil depths under conservation tillage - Hong-Xuan Duan; Yu-Gang Tian; Cheng-Ze Yang; Qing Luo; Yang Liu; Zhi-Yan Hou; Rattan Lal; Yash Pal Dang; Zhi Dong; Xin Zhao; Hai-Lin Zhang (Applied Soil Ecology, 2026)

Role of NADPH oxidase generated O2− in seed germination and cold stress response of Brassica napus - Wei-liang Qi; Guo-yan Bao; Mei-ying Sun; Wen-juan Ma; Xuan-ting Yang; Xiang-hong Gao; Miao-xin Zhou; Qi-lin Wang (Protoplasma, 2026)

Cretaceous sediment provenance, dispersal systems, and tectono-paleogeography of the western Tarim Basin, Northwest China: Far-field effects of Neo-Tethyan flat subduction - Hong-Xiang Wu; Feng-Qi Zhang; Cai-Yun Wang; Xiao-Gan Cheng; Kai-Xuan An; Yildirim Dilek; Cai Chen; Yu-Qing Zhang; Xiu-Bin Lin; Shuan-Hong Zhang; Han-Lin Chen (Global and Planetary Change, 2026)

Short-term hot spring balneotherapy ameliorates sleep disorders: wrist-worn wearable-assessed sleep improvement associated with neuroimmune, tryptophan metabolic and gut microbiome alterations - Xiao Zhang; Yue Zou; Xiao-qin He; Yi-hang Xu; Hong-xia Li; Fen Yang; Bao-chao Zhang; Lin-xuan Liao; Meng-xi Cao; Rui-xue Wang; Si-fan Hao; Meng-meng Wang; et al. (International Journal of Biometeorology, 2026)

Building performance evaluation of double-skin facade with thermotropic glazing in a reference office room of China - Xiaoqiang Hong; Xia Deng; Yilin You; Weiqiang Liu; Xuan Yang; Ruiyang Yang; Chenyuan Zheng; Yuehua Lin; Feng Shi (Energy and Buildings, 2026)

Gene-Environment Interaction of Rims1 and Adolescent Social Isolation on Schizophrenia-Like Behaviors in Mice - Lian-Hong Lin; Wei-Min Li; Qian-Yun Wu; Shuang-Yan Li; Xu-Xuan Ma; Yuan Xu; Si-Fu Deng; Bin Zhang; Ji-Hong Liu (Neuroscience Bulletin, 2026)

Targeting PTGS2/NF-κB Pathway: MG-132’s Role in Reducing Ischemic Stroke Injury - Yong-Sheng Wang; Yuan-Cheng Huang; Yong-Qi Wang; Yi-Xuan Zheng; Ying-Ren Gao; Min-Xia Wu; Fang-Hong Gao; Hong-Zhang Wang; Kun Liu; Lin Yan (Biochemical Genetics, 2026)

Recombinant bovine lactoferrin ameliorates cold stress-induced immunosuppression by modulating the gut microbiota in mice - Lin-Lin Ding; Haiyan Sun; Xuan-Yi Xu; Yu Zhang; Ai-Mei Liao; Yin-Chen Hou; Ji-Hong Huang; Long Pan (Food Bioscience, 2026)

Isolation and characterization of the novel lytic Bacillus subtilis phage vB_Bsu_W1188 revealing a wall teichoic acid glycosylation-dependent resistance mechanism - Miao Wang; Guanhua Xuan; Hong Lin; Jingxue Wang (Archives of Virology, 2026)

Concurrent removal of cetirizine hydrochloride and biodiesel accumulation in Chlorella vulgaris - Wen-Bo Yan; Zhong-Hong Zhang; Guo-Hui He; Jia-Xuan Tang; Hui-Lin Guo; Yi-Fan Zhan; Wei-Dong Yang; Hong-Ye Li; Xiang Wang (Journal of Hazardous Materials, 2026)

Insecticide resistance monitoring and identification of ryanodine receptor mutations driving diamide resistance in Cnaphalocrocis medinalis - Hong-Shuang Li; Pin-Xuan Lin; Meng-Zhen Wang; Bei-Bei Dong; Cong-Fen Gao; Shun-Fan Wu (Pesticide Biochemistry and Physiology, 2026)

Rice SINA E3 ligases dichotomously control ERECTA1 ubiquitination and stability to regulate panicle morphogenesis and grain yield - Zi-Qi Lu; Tao Guo; Ying-Jie Cao; Jun-Xiang Shan; Wang-Wei Ye; Nai-Qian Dong; Yi Kan; Yi-Bing Yang; Shuang-Qin Guo; Jie-Jie Lei; Xiao-Rui Mu; Ji-Fu Zhou; et al. (Molecular Plant, 2026)

Isomeric halide engineering of self-assembled hole-selective layers for efficient indoor perovskite photovoltaics - Zhong-En Shi; Yi-Ting Hong; Cheng-Chieh Lu; Po-Cheng Shih; Shih-I Lu; Hsiao-Chi Hsieh; Sie-Rong Li; Yu-Che Lin; Zheng-Xuan Cai; Yan-Duo Lin; Chih-Ping Chen (Chemical Engineering Journal, 2026)

PQS signaling and temperature variation modulate phage infection in Pseudomonas aeruginosa: Implications for foodborne pathogen control - Yinfeng Wang; Jiuna Kong; Yating Chen; Hong Lin; Xiuping Jiang; Guanhua Xuan; Jingxue Wang (International Journal of Food Microbiology, 2025)

Decades’ progress and prospects on maize functional genomics and molecular breeding - Qing Li; Jinsheng Lai; Jian Chen; Lin Li; Weibin Song; Beibei Xin; Hainan Zhao; Yingjie Xiao; Feng Tian; Gang Li; Yameng Liang; Lei Liu; et al. (Science China Life Sciences, 2025)

Smartphone-assisted Ce-POM/CuBTC peroxidase-like colorimetric detection of H2O2 and ascorbic acid in food samples - Yiyi Zhang; Haibo Zhang; Chengyuan Ma; Yihang Yang; Xuan Mo; Yuan Shi; Zhijia Yin; Hong Li; Lin Sun (Food Chemistry, 2025)

From growth to decline: The dynamic effects of maize-based cropping systems on soil organic carbon storage in Northeast China - Jin-Sai Chen; Zhuo Shi; Yu-Gang Tian; Hao-Ran Li; Hong-Xuan Duan; Zhi-Heng Qin; Jia Cheng; Yash Pal Dang; Bai-Jian Lin; Xin Zhao; Hai-Lin Zhang (Agriculture, Ecosystems & Environment, 2025)

Prevalence and genetic analysis of porcine circovirus type 3 (PCV3) in Henan Province of China during 2022-2024 - Lin-Lin Chen; Hao Li; Xuan-Ang Wang; Lan-Lan Zheng; Shi-Jie Ma; Hong-Ying Chen (Archives of Virology, 2025)

Machine learning-assisted dual-mode hydrogel sensor for the detection of nitrite - Si-Qi Yang; Bao-Zhu Jia; Jie Liu; Fan-Xuan Gong; Hong Wang; Hong-Tao Lei; Zhen-Lin Xu; Lin Luo (Chemical Engineering Journal, 2025)

Rheinheimera fenheensis sp. nov., Isolated from Fenhe River Basin, China - Xuan Shao; Yun-Lin Peng; Jin-Hang Guo; Zhao-Tong Chen; Hua-Ming Zhong; Di Meng; Hong-Jian Hou; Xi-Ying Zhang; Yong Zhao; Yi Li (Current Microbiology, 2025)

Mitigation of the toxic effects of nitrite: Role and mechanism of isoleucine in mitigating mitochondrial DNA leakage-induced inflammation in grass carp (Ctenopharyngodon idella) under nitrite exposure - Kai-Xuan Ren; Lin Feng; Pei Wu; Yang Liu; Hong-Mei Ren; Xiao-Wan Jin; Cheng-Bo Zhong; Xiao-Qiu Zhou; Wei-Dan Jiang (Journal of Hazardous Materials, 2025)

Tunable containing malononitrile AIEgens with reversible mechanochromic behaviors and promising applications - Guang Yang; Wen-Xuan Zhao; Ling Liang; Zeng-Min Xue; Fei Meng; Yu-Qing Kong; Hong-Tao Lin; Shu-Hai Chen; Chuan-Zeng Wang (Chemical Engineering Journal, 2025)

Near-complete recovery of phosphorus from fresh human urine: Combining magnesium-air fuel cells with modified granular attapulgite - Lin-Jiang Zhong; Lin-Feng He; Hao-Ran Yang; Shu-Jie Hu; Di Wu; Meng-Yue Zhang; Ying Chen; Xuan Zhao; Hong Liu; Yuan Liu (Journal of Environmental Management, 2025)

Harnessing microalgae: Pioneering strategies for cost-effective EPA synthesis - Yi-Ting Shen; Zi-Xu Zhang; Xin Qi; Hong-Xuan Wu; Yan-Cheng Lin; Wang Ma; Guang Yang; Xiao-Man Sun (Food Bioscience, 2025)

Energy-saving and visual-thermal performance of multi-sectional DSF system in a typical office room across five climate zones in China - Feng Shi; Chenyuan Zheng; Junwei Lin; Xuan Yang; Yilin You; Mengsheng Yang; Xiaoqiang Hong (Building and Environment, 2025)

Interfacial engineered biomass-derived G/VMT-PCNCs networks as high-performance proton-conducting humidity sensors - Lirong Tang; Junwei Wu; Zhiyi Cao; Qiqi Hong; Fengcai Lin; Ningning Tan; Lan Zhao; Xinda You; Beili Lu; Xuan Yang; Biao Huang; Hanyang Liu (Carbohydrate Polymers, 2025)

Association between sleep quality and serum biomarkers among long-term hot spring bathers: a cross-sectional study - Fen Yang; Yue Zou; Ying-ying Zhang; Hong-xia Li; Yi-hang Xu; Bao-chao Zhang; Lin-xuan Liao; Meng-xi Cao; Rui-xue Wang; Yuan Yuan; Yun Zhou; Da-yong Zeng; et al. (International Journal of Biometeorology, 2025)

Complete genome analysis and biological characterization of phage vB_Bsu_hmny2 infecting Bacillus subtilis - Qihong Liu; Guanhua Xuan; Yinfeng Wang; Hong Lin; Jingxue Wang (Archives of Virology, 2025)

Five brasilane-type sesquiterpenoids with neuroprotective activities from Xylaria nigripes - Hong-Ping Long; Xi Zhou; Si-Qian Zhou; Lan-Qing Li; Ai-Lin Liang; Wen-Yu Lu; Wen-Xuan Wang; Shao Liu; Jing Li; Ji-Kai Liu (Phytochemistry, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Tuning photoluminescence and electroluminescence of multi-resonance thermally activated delayed fluorescence emitters through peripheral donor modification for highly efficient deep-blue OLEDs - Chen-Lu Hou; Sai Guo; Yu-Fu Sun; Jia-Xuan Hu; Hong-Jin Liao; Xiao Li; Fu-Lin Lin; Lingyi Meng; Xu-Lin Chen; Can-Zhong Lu (Chemical Engineering Journal, 2025)

Aggregative Infestation of Nine Bostrichidae Species on the Madagascar Almond Tree, Terminalia neotaliala Capuron (Myrtales: Combretaceae) - Xiao-Lu Cao; Li Yu; Jian-Song Wei; Qiu-Hong Tao; Qian Lu; Wan-Xuan Wei; Xia-Lin Zheng (Neotropical Entomology, 2025)

Insight into volatile metabolites and key odorants in black teas processed from Jianghua Kucha tea germplasm (Camellia sinensis var. assamica cv. Jianghua) - Ying-Lin Zhu; Wei-Xuan Li; Yu-Hui Zhang; Han Yan; Long-Yu Guo; Yue Zhang; Hai-Peng Lv; Ling-Hong Zhou; Zhi Lin; Wen-Liang Wu; Yin Zhu (Food Chemistry, 2025)

NLRX1 in fish: A negative regulator of innate immunity during Edwardsiella piscicida infection via targeting TRAF6 through the NACHT domain - Binliang Wang; Xuan Lan; Sihan Lin; Hong Xu; Xiaodong Zhang; Junxia Yin; Yiwei Hu (Aquaculture, 2025)

Strategies for crop straw management in China's major grain regions: Yield-driven conditions and factors influencing the effectiveness of straw return - Jia Cheng; Bai-Jian Lin; Jin-Sai Chen; Hong-Xuan Duan; Yuan-Feng Sun; Xin Zhao; Yash Pal Dang; Zhi-Yu Xu; Hai-Lin Zhang (Resources, Conservation and Recycling, 2025)

Recent progress on triterpenoid derivatives and their anticancer potential - Zi-Xuan Zhao; Qiong-Yu Zou; Ying-Hong Ma; Susan L. Morris‐Natschke; Xiang-Yuan Li; Lin-Chun Shi; Guo-Xu Ma; Xu‐Dong Xu; Mei‐Hua Yang; Zi-Jian Zhao; Yuan-Xiang Li; Jing Xue; et al. (Phytochemistry, 2025)

Deciphering the distinct roles of polyketide synthase subunits in polyunsaturated fatty acid and lipid accumulation in Schizochytrium sp. - Hong-Xuan Wu; Wen-Qian Yang; Zi-Xu Zhang; Yan-Cheng Lin; Wang Ma; Xiao-Man Sun; He Huang (Food Bioscience, 2025)

Carbonate precipitation-derived CO2 outgassing offsets the mineral weathering sink in the orogenic regime of southwestern Taiwan: Insights from triple Sr isotopes - Hou-Chun Liu; Yun-Cian Lin; Yan-Hong Chen; Meng-Xuan Li; Chen-Feng You; Kuo-Fang Huang; Wei-Jen Huang; Hung-Chun Chao (Science of The Total Environment, 2024)

Revealing the links between hair metal(loids) and alterations in blood pressure among children in e-waste recycling areas through urinary metabolomics - Hong-Xuan Kuang; Ye Liu; Jia-Rong Wang; Meng-Yang Li; Yang Zhou; Lin-Xue Meng; Ming-Deng Xiang; Yun-Jiang Yu (Science of The Total Environment, 2024)

A TT1–SCE1 module integrates ubiquitination and SUMOylation to regulate heat tolerance in rice - Hong-Xiao Yu; Ying-Jie Cao; Yi-Bing Yang; Jun-Xiang Shan; Wang-Wei Ye; Nai-Qian Dong; Yi Kan; Huai-Yu Zhao; Zi-Qi Lu; Shuang-Qin Guo; Jie-Jie Lei; Ben Liao; et al. (Molecular Plant, 2024)

Isolation, characterization, and application of a novel Pseudomonas fluorescens phage vB_PF_Y1-MI in contaminated milk - Guanhua Xuan; Xianjun Liu; Yinfeng Wang; Hong Lin; Xiuping Jiang; Jingxue Wang (Molecular Genetics and Genomics, 2024)

Alendronate sodium induces G1 phase arrest and apoptosis in human umbilical vein endothelial cells by inhibiting ROS-mediated ERK1/2 signaling - Yi Feng; Shao-Qin Tu; Yu-Luan Hou; Yi-Ting Shao; Lin Chen; Zhi-Hui Mai; Yu-Xuan Wang; Jia-Ming Wei; Sai Zhang; Hong Ai; Zheng Chen (Toxicology, 2024)

Hydrology controls sulfuric acid-mediated weathering in an orogenic regime of southwestern Taiwan - Hou-Chun Liu; Meng-Xuan Li; Chen-Feng You; Yan-Hong Chen; Kuo-Fang Huang; Chuan-Hsiung Chung; Guan-Wei Lin (Science of The Total Environment, 2024)

Most appropriate nozzle of six-rotor UAV for prescribed spraying liquid in tea plantation under effects of downwash flow structure in hover - Nai-Hong Hu; Wen-Xuan Zhou; Lin Zhu; Yan-Cheng Li; Xin-Yu Xie; Ru-Yan Hou; Cheng-Long Yin (Crop Protection, 2024)

Optimizing straw and nitrogen fertilizer resources for low-carbon sustainable agriculture - Bai-Jian Lin; Jia Cheng; Hong-Xuan Duan; Wen-Xuan Liu; Yash Pal Dang; Xin Zhao; Hai-Lin Zhang (Resources, Conservation and Recycling, 2024)

Comprehensive insights into the refractory melanoidins production from structural extracellular polymeric substances via thermal hydrolysis pretreatment and the inhibition on anaerobic fermentation - Si-Di Hong; Shuai Wang; Xiao-Fei Yang; Xing-Chen Huang; Jia-Xiang Xiao; Wen-Xuan Wang; Jiahuan Tang; Hao Lin; Raymond Jianxiong Zeng; Kun Dai; Fang Zhang (Chemical Engineering Journal, 2024)

Bacteriophage-encoded protein utilization in bacterial ghost production: a mini-review - Guanhua Xuan; Dongdong Qiu; Yinfeng Wang; Jingxue Wang; Hong Lin (World Journal of Microbiology and Biotechnology, 2024)

Genotoxicity and cytotoxicity in male reproductive cells caused by sediment pollutants - Meng-Wei Lin; Jai-Yu Chen; Yu-Xuan Ye; Wei-Yi Chen; Hong-Lin Chan; Hsiu-Chuan Chou (Science of The Total Environment, 2024)

Occurrence and fate of pharmaceutical pollutants in wastewater: Insights on ecotoxicity, health risk, and state–of–the-art removal - Minh-Ky Nguyen; Chitsan Lin; Xuan-Thanh Bui; Md. Refat Jahan Rakib; Hoang-Lam Nguyen; Quoc-Minh Truong; Hong-Giang Hoang; Huu-Tuan Tran; Guilherme Malafaia; Abubakr M. Idris (Chemosphere, 2024)

Whole-genome sequencing of Escherichia coli from retail meat in China reveals the dissemination of clinically important antimicrobial resistance genes - Qin Wang; Ying-Yue Han; Tie-Jun Zhang; Xuan Chen; Heng Lin; Hong-Ning Wang; Chang-Wei Lei (International Journal of Food Microbiology, 2024)

Identifying the source and fate of boron in geothermal water: Evidence from B/Na and B isotopes - Ying Tan; Xiao-Wei Jiang; Tao-Tao Ji; Yin-Fei Luo; Wan Dai; Hong Zhang; Zhao-Xuan Niu; Yu-De Lei; Zhi-Yuan Zhang; Tian-Yi Lin; Hua-Ming Guo (Science of The Total Environment, 2024)

Brunonianines A-C, C20-diterpenoid alkaloids with cyano group from Delphinium brunonianum Royle - Qing Li; Zhi-Wei Wang; Mu-Xuan Wang; Hao-Lin Yu; Lei Chen; Zhuoer Cai; Yu Zhang; Min-Min Gu; Yuan-Ling Shao; Hong-Ping Han; Zhi-Xin Liao (Phytochemistry, 2024)

Perturbation of lipid metabolism in 3T3-L1 at different stages of preadipocyte differentiation and new insights into the association between changed metabolites and adipogenesis promoted by TBBPA or TBBPS - Yun-Jiang Yu; Jing-Lin Tian; Tong Zheng; Hong-Xuan Kuang; Zong-Rui Li; Chao-Jie Hao; Ming-Deng Xiang; Zhen-Chi Li (Journal of Hazardous Materials, 2024)

Benzoquinone and furopyridinone derivatives from the marine-derived fungus Talaromyces sp. MCCC 3A01752 - Xuan Hong; Lingzhi Tang; Zhongwei Chen; Qiliang Lai; Beibei Zhang; Youwei Jiang; Xunjie Wang; Ruonan He; Jianhui Lin; Zongze Shao; Shan Lin; Weiyi Wang (Natural Product Research, 2024)

A model of hybrid speciation process drawn from three new poplar species originating from distant hybridization between sections - Yu-Jie Shi; Jin-Liang Huang; Jia-Xuan Mi; Jing Li; Fan-Yu Meng; Yu Zhong; Fang He; Fei-Fei Tian; Fan Zhang; Liang-Hua Chen; Han-Bo Yang; Hong-Lin Hu; et al. (Molecular Phylogenetics and Evolution, 2024)

Vacuolar H+-ATPase and BZR1 form a feedback loop to regulate the homeostasis of BR signaling in Arabidopsis - Yu-Tong Jiang; Lu-Han Yang; Ji-Xuan Zheng; Xian-Chen Geng; Yu-Xuan Bai; Yu-Chen Wang; Hong-Wei Xue; Wen-Hui Lin (Molecular Plant, 2023)

Sulforaphane alleviates the meiosis defects induced by 3-nitropropionic acid in mouse oocytes - Wei-Jian Li; Xuan Zhang; Ming Shen; Hong-Lin Liu; Li-Ren Ding (Food and Chemical Toxicology, 2023)

Analysis of the spatial-temporal evolution of Green and low carbon utilization efficiency of agricultural land in China and its influencing factors under the goal of carbon neutralization - Jun Fu; Rui Ding; Yu-qi Zhu; Lin-yu Du; Si-wei Shen; Li-na Peng; Jian Zou; Yu-xuan Hong; Juan Liang; Ke-xin Wang; Wen-qian Xiao (Environmental Research, 2023)

Extended exposure to tetrabromobisphenol A-bis(2,3-dibromopropyl ether) leads to subfertility in male mice at the late reproductive age - Yuan-Yuan Li; Yi-Ming Xiong; Xuan-Yue Chen; Jia-Yi Sheng; Lin Lv; Xing-Hong Li; Zhan-Fen Qin (Archives of Toxicology, 2023)

Genome-centric metagenomics provides new insights into metabolic pathways of polyhydroxyalkanoates biosynthesis and functional microorganisms subsisting on municipal organic wastes - Ruo-hong Li; Jin Huang; Cheng-xi Liu; Ke Yu; Feng Guo; You Li; Zuo-hong Chen; Xuan Wang; Ren-xin Zhao; Jia-yu Zhang; Jia-jin Liang; Yun Li; et al. (Water Research, 2023)

Opportunities and challenges for ribosome-inactivating proteins in traditional Chinese medicine plants - Yi-xuan Yang; Xin-yi Wang; Tong Lin; Yu Sun; Yi-cheng Yu; Zhen-hong Zhu (Toxicon, 2023)

Towards effective recovery of humate as green fertilizer from landfill leachate concentrate by electro-neutral nanofiltration membrane - Wenyuan Ye; Mingqiu Hong; Xuan Huang; Tianci Chen; Ailiang Gu; Xiaocheng Lin; Xuewei Li; Xiangrong Chen; Dong Han Seo; Shuaifei Zhao; Xueming Chen; Bart Van der Bruggen; et al. (Science of The Total Environment, 2023)

The molecular basis of heat stress responses in plants - Yi Kan; Xiao-Rui Mu; Jin Gao; Hong-Xuan Lin; Youshun Lin (Molecular Plant, 2023)

Quorum sensing autoinducers AHLs protect Shewanella baltica against phage infection - Guanhua Xuan; Lin Tan; Yuqing Yang; Jiuna Kong; Hong Lin; Jingxue Wang (International Journal of Food Microbiology, 2023)

GABAergic Neurons in the Nucleus Accumbens are Involved in the General Anesthesia Effect of Propofol - Jing Yan; Bei-Ning Hang; Lin-Hui Ma; Jia-Tao Lin; Yue Zhou; Xin-Hao Jiao; Ying-Xuan Yuan; Ke-Jie Shao; Le-Meng Zhang; Qi Xue; Zi-Yi Li; Hong-Xing Zhang; et al. (Molecular Neurobiology, 2023)

Characterization of a novel phage vB_Pae_HB2107-3I that infects Pseudomonas aeruginosa - Jiuna Kong; Guanhua Xuan; Hong Lin; Jingxue Wang (Molecular Genetics and Genomics, 2023)

SWD1 epigenetically chords fungal morphogenesis, aflatoxin biosynthesis, metabolism, and virulence of Aspergillus flavus - Xiaohua Pan; Ling Hao; Chi Yang; Hong Lin; Dandan Wu; Xuan Chen; Mengjuan Zhang; Dongmei Ma; Yu Wang; Wangzhuo Fu; Yanfang Yao; Shihua Wang; et al. (Journal of Hazardous Materials, 2023)

U-shaped association between low-density lipoprotein cholesterol levels and risk of all-cause mortality mediated by post-stroke infection in acute ischemic stroke - Zi-Mo Chen; Hong-Qiu Gu; Jing-Lin Mo; Kai-Xuan Yang; Ying-Yu Jiang; Xin Yang; Chun-Juan Wang; Jie Xu; Xia Meng; Yong Jiang; Hao Li; Li-Ping Liu; et al. (Science Bulletin, 2023)

Simultaneous detection and phylogenetic analysis of porcine epidemic diarrhea virus and porcine circovirus 4 in Henan province, China - Hong-Xuan Li; Xi-Meng Chen; You-Yi Zhao; Hong-Lei Zhang; Lan-Lan Zheng; Lin-Qing Wang; Shi-jie Ma; Hong-Ying Chen (Archives of Virology, 2023)

Ultralight, robust, and high Prussian blue-loading polyacrylonitrile aerogel: Preparation, characterization and efficient adsorption/removal of Cs+ - Xiao-Bo Yang; Wei Li; Ze-Zhong Lin; Jing-Qi Liu; Hong-Xin Jiang; Hao Jia; Wei-Liang Jin; Xin-Long Hou; Bing-Xuan Du; Li-Na Zhu; De-Ming Kong (Chemical Engineering Journal, 2023)

Deciphering basic and key traits of antibiotic resistome in influent and effluent of hospital wastewater treatment systems - Lin Zhu; Ling Yuan; Xin-Yi Shuai; Ze-Jun Lin; Yu-Jie Sun; Zhen-Chao Zhou; Ling-Xuan Meng; Feng Ju; Hong Chen (Water Research, 2023)

Investigation of biochar amendments on odor reduction and their characteristics during food waste co-composting - Minh Ky Nguyen; Chitsan Lin; Hong Giang Hoang; Xuan Thanh Bui; Huu Hao Ngo; Van Giang Le; Huu-Tuan Tran (Science of The Total Environment, 2023)

Characterization of procyanidin extracts from hawthorn (Crataegus pinnatifida) in human colorectal adenocarcinoma cell line Caco-2, simulated Digestion, and fermentation identified unique and novel prebiotic properties - Xue Han; Qian Zhou; Zhe Gao; Guanying Bianca Xu; Hong Chen; Bimal Chitrakar; Yasai Sun; Wen Zhao; Xuan Lin; Kaixuan Zhou; Zhisheng Zhang (Food Research International, 2023)

Preferred prey reduce species realized niche shift and improve range expansion prediction - Lixia Han; Zhixin Zhang; Weishan Tu; Qing Zhang; Yanhua Hong; Shengnan Chen; Zhiqiang Lin; Shimin Gu; Yuanbao Du; Zhengjun Wu; Xuan Liu (Science of The Total Environment, 2023)

Detection and genetic analysis of porcine circovirus-like virus in pigs with diarrhea between 2016 and 2021 in Henan and Shanxi provinces of China - Liu-Hui Zhang; Lin-Qing Wang; Hong-Xuan Li; Hong-Lei Zhang; Lan-Lan Zheng; Xi-Meng Chen; Hong-Ying Chen (Archives of Virology, 2023)

Photocatalytic degradation of dissolved organic matter in landfill leachate by heterostructural ZnO-rGO composite catalysts - Bicai Li; Xuan Lin; Ziying Qi; Meng Dong; Caiyun Gao; Hong Zhang; Zhicheng Li (Environmental Science and Pollution Research, 2023)

Biodegradation of high di-(2-Ethylhexyl) phthalate (DEHP) concentration by food waste composting and its toxicity assessment using seed germination test - Huu-Tuan Tran; Chitsan Lin; Su Shiung Lam; Thi Hieu Le; Hong-Giang Hoang; Xuan-Thanh Bui; Eldon R. Rene; Po Han Chen (Environmental Pollution, 2023)

PLXDC2 enhances invadopodium formation to promote invasion and metastasis of gastric cancer cells via interacting with PTP1B - Bin Wu; Yan-xia Wang; Jun-jie Wang; Dong-fang Xiang; Meng-si Zhang; Ze-xuan Yan; Wen-ying Wang; Jing-ya Miao; Xi Lan; Jia-jia Liu; Zheng-yan Li; Chuan Li; et al. (Clinical & Experimental Metastasis, 2022)
Plexin-domain containing 2 (PLXDC2) has been reported as an oncoprotein in several human malignancies. However, its expression and roles in gastric cancer remain largely unclear. In this study, we found that PLXDC2 was highly expressed in gastric cancer tissues, and the expression levels were positively correlated with clinicopathological features, but negatively with the patients’ outcome. Cox regression analysis identified PLXDC2 as an independent prognostic indicator for the patients. Knockdown of PLXDC2 markedly suppressed the in vitro invasion and in vivo metastasis of gastric cancer cells, while overexpression of PLXDC2 resulted in opposite effects. Mechanistically, PLXDC2 enhanced the level of phosphorylated Cortactin (p-Cortactin) by physically interacting with protein tyrosine phosphatase 1B (PTP1B), an important dephosphorylase, to prevent its dephosphorylating of p-Cortactin, thereby promoting the formation of invadopodia. Collectively, our results indicate that PLXDC2 contributes to the invasion and metastasis of gastric cancer by inhibiting PTP1B to facilitate the invadopodium formation, and may serve as a potential prognostic biomarker and a therapeutic target for this disease.

Sex differences in microstructural alterations in the corpus callosum tracts in drug-naïve children with ADHD - Qingxia Lin; Xuan Bu; Hong Chen; Yan Liang; Weiqian Wang; Yanhong Yi; Haixi Lin; Lu Lu; Yingxue Gao; Andan Qian; Shuangli Chen; Meihao Wang; et al. (Brain Imaging and Behavior, 2022)

Lelliottia steviae sp. nov. isolated from Stevia rebaudiana Bertoni - Jing Lin; Ke Huang; Jing-Yu Huang; Yuan-Ru Xiong; Meng-Meng Wei; Na Xiao; Jia Gao; Xuan-Kai Ding; Zi-Yang Ma; Jun-Hao Sang; Ling-Xian Kong; Zhi-Yun Hong; et al. (Archives of Microbiology, 2022)

Structure elucidation of a novel cyclic tripeptide from the marine-derived fungus Aspergillus ochraceopetaliformis DSW-2 - Yanyan Liao; Xuan Hong; Jing Yang; Jiang-Jiang Qin; Beibei Zhang; Jianhui Lin; Zongze Shao; Weiyi Wang (Natural Product Research, 2022)

Advanced Treatment Technologies for the Removal of Organic Chemical Sunscreens from Wastewater: a Review - ‬Huu-Tuan Tran; Bao-Trong Dang; Le Thi Thu Thuy; Hong-Giang Hoang; Xuan-Thanh Bui; Van-Giang Le; Chitsan Lin; Minh-Ky Nguyen; Kim-Qui Nguyen; Phuong-Thao Nguyen; Quach An Binh; Thi-Phuong Thuy Bui (Current Pollution Reports, 2022)

Complete genome analysis of the novel Shewanella phage vB_Sb_QDWS - Lin Tan; Guanhua Xuan; Hong Lin; Jingxue Wang (Archives of Virology, 2022)

Complete genome analysis of the newly isolated Vibrio phage vB_VpP_WS1 of the family Microviridae - Wenjing Xu; Guanhua Xuan; Hong Lin; Jingxue Wang (Archives of Virology, 2022)

An efficient genetic manipulation protocol for dark septate endophyte Falciphora oryzae - Zhen-Zhu Su; Meng-Di Dai; Jia-Nan Zhu; Yu-Lan Zeng; Xuan-Jun Lu; Xiao-Hong Liu; Fu-Cheng Lin (Biotechnology Letters, 2021)

Future variation in mountainous discharge in arid northwestern China: A basin case study - Lei Wu; Chang-bin Li; Xu-hong Xie; Jia-nan Lv; Jian-mei Wei; Xuan Zhou; Lin-shan Yang (Journal of Mountain Science, 2021)

The Individual and Synergistic Indexes for Assessments of Heavy Metal Contamination in Global Rivers and Risk: a Review - Hong-Giang Hoang; Chitsan Lin; Chow-Feng Chiang; Xuan-Thanh Bui; Wisanukorn Lukkhasorn; Thi-Phuong-Thuy Bui; Huu-Tuan Tran; Thi-Dieu-Hien Vo; Van-Giang Le; Long D. Nghiem (Current Pollution Reports, 2021)

Characteristics of bacterial community and ARGs profile in engineered goldfish tanks with stresses of sulfanilamide and copper - Benjamin Makimilua Tiimub; Zhen-chao Zhou; Lin Zhu; Yang Liu; Xin-Yi Shuai; Lan Xu; Christophe’ Niyungeko; Ling-Xuan Meng; Yu-Jie Sun; Hong Chen (Environmental Science and Pollution Research, 2021)

Assessment of heavy metal contamination and adverse biological effects of an industrially affected river - Gavin Yeh; Hong-Giang Hoang; Chitsan Lin; Xuan-Thanh Bui; Huu-Tuan Tran; Chien-Chuan Shern; Chi-Thanh Vu (Environmental Science and Pollution Research, 2020)

Aberrant white matter properties of the callosal tracts implicated in girls with attention-deficit/hyperactivity disorder - Qingxia Lin; Xuan Bu; Meihao Wang; Yan Liang; Hong Chen; Weiqian Wang; Yanhong Yi; Haixi Lin; Jiaxiu Zhou; Lu Lu; Xinyu Hu; Chuang Yang; et al. (Brain Imaging and Behavior, 2020)

Breakup unconformities at the end of the early Oligocene in the Pearl River Mouth Basin, South China Sea: significance for the evolution of basin dynamics and tectonic geography during rift–drift transition - Yue Gong; Changsong Lin; Zhongtao Zhang; Bo Zhang; Liangfeng Shu; Xuan Feng; Fanghao Hong; Zuochang Xing; Hanyao Liu; Enyu Su (Marine Geophysical Research, 2019)

Rice ecosystem services in South-east Asia - Josef Settele; Kong Luen Heong; Ingolf Kühn; Stefan Klotz; Joachim H. Spangenberg; Gertrudo Arida; Alexis Beaurepaire; Silke Beck; Erwin Bergmeier; Benjamin Burkhard; Roland Brandl; Jesus Victor Bustamante; et al. (Paddy and Water Environment, 2018)

Nanoparticle-encapsulated emodin decreases diabetic neuropathic pain probably via a mechanism involving P2X3 receptor in the dorsal root ganglia - Lin Li; Xuan Sheng; Shanhong Zhao; Lifang Zou; Xinyao Han; Yingxin Gong; Huilong Yuan; Liran Shi; Lili Guo; Tianyu Jia; Shuangmei Liu; Bing Wu; et al. (Purinergic Signalling, 2017)

Involvement of FMRP in Primary MicroRNA Processing via Enhancing Drosha Translation - Rui-Ping Wan; Lin-Tao Zhou; Hai-Xuan Yang; Yong-Ting Zhou; Shun-Hua Ye; Qi-Hua Zhao; Mei-Mei Gao; Wei-Ping Liao; Yong-Hong Yi; Yue-Sheng Long (Molecular Neurobiology, 2017)

iMem-Seq: A Multi-label Learning Classifier for Predicting Membrane Proteins Types - Xuan Xiao; Hong-Liang Zou; Wei-Zhong Lin (The Journal of Membrane Biology, 2015)

Characterisation of the dark green islands of cucumber mosaic virus infected Nicotiana tabacum - Li-Juan Chen; Jian Liu; Fei-Fei Zhao; Jing-Yi Li; Sheng-Xuan Wang; Hong-Hui Lin; De-Hui Xi (Plant Cell Reports, 2015)

Stress signaling in response to polycyclic aromatic hydrocarbon exposure in Arabidopsis thaliana involves a nucleoside diphosphate kinase, NDPK-3 - Hong Liu; David Weisman; Ling Tang; Long Tan; Wen-ke Zhang; Zong-hua Wang; Yan-he Huang; Wen-xiong Lin; Xuan-ming Liu; Adán Colón-Carmona (Planta, 2015)

G Protein-Coupled Estrogen Receptor–Protein Kinase A–ERK–CREB Signaling Pathway is Involved in the Regulation of Mouse Gubernaculum Testis Cells by Diethylstilbestrol - Xuan Zhang; Jian-hong Li; Shou-xing Duan; Qing-Jun Lin; Song Ke; Lian Ma; Tian-hua Huang; Xue-wu Jiang (Archives of Environmental Contamination and Toxicology, 2014)

Unpalatable weed Stellera chamaejasme L. provides biotic refuge for neighboring species and conserves plant diversity in overgrazing alpine meadows on the Tibetan Plateau in China - Wei Cheng; Geng Sun; Lin-fang Du; Yan Wu; Qun-ying Zheng; Hong-xuan Zhang; Lin Liu; Ning Wu (Journal of Mountain Science, 2014)

CD24 mediates gastric carcinogenesis and promotes gastric cancer progression via STAT3 activation - Ying-Chao Wang; Ji-Lin Wang; Xuan Kong; Tian-Tian Sun; Hao-Yan Chen; Jie Hong; Jing-Yuan Fang (Apoptosis, 2014)

Forced expression of indoleamine-2,3-dioxygenase in human umbilical cord-derived mesenchymal stem cells abolishes their anti-apoptotic effect on leukemia cell lines in vitro - Yin Yuan; Xin Lu; Chang-li Tao; Xuan Chen; Hong-wei Shao; Shu-lin Huang (In Vitro Cellular & Developmental Biology - Animal, 2013)

Effects of single and combined genotypes of MC4R and POU1F1 genes on two production traits in Langshan chicken - Lin Jun Yan; Xing Tang Fang; Yao Liu; Chun Lei Zhang; Xuan Xuan Liu; Jing Zhao; Jing Jing Li; Hong Chen (Molecular Biology Reports, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Over-expression of the AtGA2ox8 gene decreases the biomass accumulation and lignification in rapeseed (Brassica napus L.) - Xiao-ying Zhao; Deng-feng Zhu; Bo Zhou; Wu-sheng Peng; Jian-zhong Lin; Xing-qun Huang; Re-qing He; Yu-hong Zhuo; Dan Peng; Dong-ying Tang; Ming-fang Li; Xuan-ming Liu (Journal of Zhejiang University-SCIENCE B, 2010)

Fine mapping and candidate gene analysis of spd6, responsible for small panicle and dwarfness in wild rice (Oryza rufipogon Griff.) - Jun-Xiang Shan; Mei-Zhen Zhu; Min Shi; Ji-Ping Gao; Hong-Xuan Lin (Theoretical and Applied Genetics, 2009)

Overexpression of the trehalose-6-phosphate phosphatase gene OsTPP1 confers stress tolerance in rice and results in the activation of stress responsive genes - Liang-Fa Ge; Dai-Yin Chao; Min Shi; Mei-Zhen Zhu; Ji-Ping Gao; Hong-Xuan Lin (Planta, 2008)